Prediction of human intestinal absorption using micellar liquid chromatography with an aminopropyl stationary phase. (20th March 2019) - Shokry, Dina S.; Waters, Laura J.; Parkes, Gareth M.B.; Mitchell, John C.
Abstract: The extent of human intestinal absorption (HIA) for a drug is considered to be an important pharmacokinetic parameter which must be determined for orally administered drugs. Traditional experimental methods relied upon animal testing and are renowned for being time consuming and expensive as well as being ethically unfavourable. As a result, the development of alternative methods to evaluate a drug's pharmacokinetics is crucial. Micellar liquid chromatography is considered to be one of these methods that can replace the use of animals in the prediction of HIA. In this study, the combination of an aminopropyl column with the biosurfactant sodium deoxycholate bile salt was used in the experimental determination of micelle–water partition coefficients (log P mw ) for a group of compounds. Multiple linear regression was then used for the prediction of HIA using the experimentally determined log P mw along with other molecular descriptors, leading to the construction of a model equation of R 2 = 85% and a prediction power represented by R 2 Pred. = 72%. The use of micellar liquid chromatography with an aminopropyl column in combination with sodium deoxycholate was found to be a good method for the prediction of human intestinal absorption, providing data for a far wider range of compounds compared with previous studies.